Market Integration and (the Limits of) the First Sale Rule in North American and European Trademark Law - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2011)
This Article explores the intricate relationship between the exercise of trademark rights and the free movement of goods in the marketplace, and considers the effectiveness and the limitations of the principle of trademark first sale (also known as trademark exhaustion) in promoting the free movement of goods across international borders, notably across members of free trade areas. In particular, this Article examines the application of the principle of trademark first sale and the resulting process of market integration that has characterized to date the members of NAFTA and the European Union. Based upon this comparison, this Article argues that the creation of an effective system of free movement of goods in free trade areas requires, at a minimum, the adoption of uniform national rules providing for the exhaustion of national trademark rights with respect to products lawfully distributed worldwide or, at least, in the territory of all members of those areas. This Article highlights, however, that effective market integration across free trade areas may be jeopardized when corporations can use material differences in product quality to control product distribution and prevent the free movement of goods even when members of these areas nominally permit the importation of products lawfully distributed internationally or, at least, in the territory of other members. Following the analysis of the approaches adopted by NAFTA and the European Union, this Article stresses that the convergence of national standards, the mutual recognition of product characteristics, or the acceptance into national markets of materially different products from other members carrying appropriate labels disclosing these differences can nonetheless overcome these barriers. Ultimately, this Article concludes that invoking trademark protection to segment the market against the parallel trade of genuine goods not only undermines the purpose of free trade areas; it also goes against the general scope of trademark protection, which protects consumers against confusion and trademark owners against illegitimate acts that could take unfair advantage of, or damage the reputation of, the marks, and does not include the prohibition of the resale of genuine goods that trademark owners themselves have introduced into the market, even if in the territory of another member of a free trade area.